Analysis of Flavor Composition in Different Peanut Varieties᾽ Butter - HU Jun-jing; LIU xiao-cheng; LU ze-yu; LI Jin-zhuang (Liang you shipin ke-ji, 2023)
In this paper, the flavor substances of five varieties of peanut butter were mainly studied by gas chromatography-mass spectrometry (GC-MS). The results showed that the total number of flavor substances was 62, 55, 46, 46 and 44 in “Baisha”, “Luohan”, “Kainong 80”, “Chuantong” and “Lu Hua 8”, respectively The main flavor substances of these five peanut varieties were alcohols, aldehydes, hydrocarbons and pyrazines. Among them, "Baisha" had many kinds of flavor substances, but few pyrazines, and the aroma of nuts was weak. The other four peanut butter varieties had higher pyrazines content, but “Lu Hua 8” peanut butter had a high content of acetic acid, which leads to acrimonious sour and poor aroma. Therefore, among the five peanut varieties, Kainong 80, Luohan and Chuantong were the best varieties for processing peanut butter.